Riparian shading mitigates warming but cannot revert thermal alteration by impoundments in lowland rivers - Marteau, Baptiste; Piégay, Hervé; Chandesris, André; Michel, Kristell; Vaudor, Lise (Earth surface processes and landforms, 2022)
Given the actual trajectory of greenhouse gases emissions, in situ actions are needed to limit rivers water warming. Riparian tree planting has been shown as a successful mitigation strategy, but most studies have been conducted on upland forested rivers. The hydraulic, geomorphic and thermal conditions of lowland rivers, subject to straightening and fragmentation, are very different from upland systems. In this study, the role of riparian cover relative to the presence of weirs was investigated in lowland slow‐flowing rivers within the agricultural context of the Bresse region, France. Using airborne thermal infrared (TIR) imaging, nine reaches of 20 to 30 km each were mapped to quantify water temperature, riparian vegetation and assess weir location. Campaigns were carried out during the hot summer 2018. Results have comforted that riparian vegetation is capable of limiting increase in temperature during warm events by 2 to 3°C, but with varying success depending on the rivers' thermal regimes. Rivers with a ‘colder’ regime (i.e., ground/karstwater‐fed) are thermally less influenced by riparian vegetation but also more resilient to the presence of weirs. Rivers with the highest degree of thermal alteration showed the highest positive response to riparian shading. Riparian vegetation prevents stagnant water from extreme warming but does not prevent alteration of the thermal regime, for example thermal stratification, likely to occur on a daily basis and to large extents (> 80%) during warm and low‐flow events in impounded rivers. Thermal conditions were sub‐optimal for most fish species that could be expected in these streams. Although the direct relation with thermal alteration is not proved, hydrobiological scores of flow alteration are correlated with our metric of thermo‐physical alteration. Management strategies to limit temperature increase should carefully consider restoring the thermal regime of rivers through weir removal when it is possible, combined with riparian tree planting as an additional mitigation measure. Temperature response to riparian vegetation cover (1) is controlled by both the degree of thermal alteration of a river (2) and its own thermal regime (3); In lowland rivers, shading appears most effective when flow hydraulics (and natural thermal regime) are altered; Rehabilitation strategies aiming at restoring thermal regimes via weir removal should be advocated as more likely to be effective than tree planting only.